Econometric Analysis of Industrial Country Commodity Exports - Kumar, Manmohan (IMF Working Papers; Working Paper ;, 1992)
This paper examines the composition of primary commodity exports by industrial countries and contrasts this composition with that of the exports by developing countries. Both the share of industrial countries' commodity exports in world commodity exports, as well as in their own total merchandize exports, is examined over time and across different commodities and geographical areas. The paper then specifies and empirically estimates an econometric model of the demand for and the supply of commodity exports by industrial countries. The model is estimated for five groups of industrial countries and the parameters of the model are compared with those available for the developing countries.